Effectiveness of Andrographis paniculata Extract Nanoparticle on The Expression of CD4+ and CD8+ of Rats Listeriosis - Iffiyana, Alifatul; Farida, Helmia; Susilaningsih, Neni (Program Study of Biology, Science and Technology Faculty, UIN Maulana Malik Ibrahim Malang, 2025)
Listeria monocytogenes is a Gram-positive bacterium that causes listeriosis known as foodborne disease. L. monocytogenes infection will activate both innate and adaptive immune responses. Androghrapis paniculata has an effect as immunostimulant. Nanocapsulation-chitosan can increase solubility and reduce the particle size making it easier for compounds to enter the cell. This research focuses on the utilization of nanoparticle A. paniculata as an immunomodulator against CD4+ and CD8+. Study design was an experimental study with post only control group trial. A total of 30 male Wistar rats divided into 6 groups, with 5 rats in each group. All groups were injected by L. monocytogenes intravenous except Normal Group. EAP 200 group was administered oral crude extract of A. paniculata at dose 200 mg/kg BW for 7 days. nEAP 100, nEAP 200 and nEAP 400 groups were administered oral Nanoparticle-Extract of A. paniculata at dose of 100 mg/kg BW, 200 mg/kg BW, and 400 mg/kg BW respectively for 7 days. CD4+ and CD8+ cells were detected by isolating PBMC cells then analyzed using flow cytometry. Statistical analysis applied ANOVA. Both crude extract of EAP 200 and nanoparticles nEAP 400 significantly increase the number of CD4+ (P= 0.050) and CD8+ (P= 0.010). Crude and nanoparticles extract of A. paniculata increase the production of CD4+ and CD8+ cells in rats infected with L. monocytogenes.